Certain Subclass of Univalent Functions Involving Fractional Q-Calculus Operator - HAMEED, Mustafa Ibrahim (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
The main object of the present paper is to introduce certain subclass of univalent function associated with the concept of differential subordination. We studied some geometric properties like coefficient inequality and nieghbourhood property, the Hadamard product properties and integral operator mean inequality.